Action, Norm, unjust and unwise Crime (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
In this article we analyze the concepts of ‘norm’ and ‘wrong’ that better serve theaims of Criminal Law. The author defends that it is more precise to break in to two parts the concept of ‘the contrary to the norm’, attaching to the concept of ‘wrong’ the mere objective contradiction of the act with the content of the determinating norm (promulgated norm), which leaves ‘culpability’ the problem of “individual communication”. As a result, the concept of ‘wrong’ collaborates with the joint aim of protecting legally protected interests through positive general prevention in its original use, since the concept attempts to transmit the general valuations of the conduct and the legally protected interests that would be lost when introducing the ‘categoryof wrong’ the considerations relative to the individual capacity to act according tothose general parameters.Thus the author rejects the constructions that currently defend the individualization of the due care to the scope of the concept of ‘wrong’, or because they assume that the concept of ‘wrong’ as an infraction of the vigilence of the norm, or, in othercases, because, in spite of conceiving the concept of ‘wrong’ as an infraction of a determination norm, they include in the concept of ‘wrong’ certain requirements of the norm-communication. All of them have an inadmissible derogation of the general norms of conduct in criminal negligence and the loss of the positive general preventive function of the ‘category of wrong.’
Keywords: Norm; wrong; due care; criminal negligence